Modernism and cosmology : absurd lights - Ebury, Katherine, 1986- (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2014)
"In Modernism and Cosmology, Yeats, Joyce and Beckett are examined as test cases for modernist aesthetic responses to a new cosmology. Katherine Ebury teases out the reception of Einstein's cosmology in modernist literary culture, both locally and globally. Detailed close readings of the key works of Yeats, Joyce and Beckett are used to develop alternative reading models of texts such as Finnegans Wake and 'The Trilogy'; within these texts we find multiple references to binary stars, nebulae, the Big Bang Theory, the space-time continuum and the Expanding Universe and many other key concepts of the 'mysterious universe' of the new physics, providing insights into their difficulty, absurdity and beauty. Careful attention to contemporary popularisations allows us to achieve a measure of the intellectual toolbox with which these modernist writers equipped themselves and to understand their creative transformations of this material"--
Machine generated contents note: -- 1.Introduction: Cosmic Modernism 2.Yeatsian Cosmology3.Joycean Cosmologies4.Beyond the Rainbow: Spectroscopy in the Wake5.The Beckettian Cosmos6.Stars and Atoms in 'The Trilogy' Epilogue - International Modernism Bibliography Index.
Includes bibliographical references (pages 190-204) and index.
Keywords: English literature -- 20th century -- History and criticism; Modernism (Literature); Cosmology in literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh